Arthritis in a human T lymphotropic virus type I (HTLV-I) carrier. Issue 9 (September 1990) - Ijichi, S; Matsuda, T; Maruyama, I; Izumihara, T; Kojima, K; Niimura, T; Maruyama, Y; Sonoda, S; Yoshida, A; Osame, M
Abstract : The case is described of a 57 year old woman with polyarthritis fulfilling the 1987 revised criteria of the American Rheumatism Association for rheumatoid arthritis, accompanied by clinical carrier state infection of HTLV-I. Anti-HTLV-I IgM antibodies were detected by western blot analysis in her synovial fluid and serum. Atypical lymphocytes with nuclear convolutions were found in synovial fluid and synovial tissue obtained from the affected knee joint, suggesting in situ activation of HTLV-I infected lymphocytes in the affected synovial compartment. The HTLV-I antigens were detected (1.2%) in short term cultured synovial fluid lymphocytes, by indirect immunofluorescence. These findings supported the possibility that HTLV-I has a role in triggering or modifying inflammation in the synovial compartment.